LITERATURE REVIEW ABOUT PLANNED HAPPENSTANCE - Rusandi, M. Arli (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2024)
The fast-changing and uncertain era demands an adaptive approach to career development. ‘Planned happenstance’ or events that are unexpected but planned has become an essential instrument in the course of a career. In this context, ‘planned happenstance’ is defined as being open to unexpected changes and opportunities that can potentially change career paths. The essence of this approach is to reduce anxiety about the future, learn throughout life, and exploit and create favorable unexpected events. Its main aspects include curiosity, perseverance, flexibility, optimism, and courage. Indicators of the success of implementing ‘planned happenstance’ include the individual’s ability to turn unexpected events into learning opportunities, take advantage of uncertainty as an opportunity, and, ultimately, create a fulfilling and meaningful career path. This literature review explores the application and implications of this concept in various contexts, such as education, professional development, and schoolwork transition. We conclude that ‘planned happenstance’ is an essential component of the career path, and more research is needed to explore how education and training can more effectively integrate this concept.